2009
DOI: 10.1016/j.molcel.2009.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic PER Abundance Defines a Critical Nodal Point for Negative Feedback within the Circadian Clock Mechanism

Abstract: Summary Circadian rhythms in mammals are generated by a transcriptional negative feedback loop that is driven primarily by oscillations of PER and CRY, which inhibit their own transcriptional activators, CLOCK and BMAL1. Current models posit that CRY is the dominant repressor while PER may play an accessory role. In this study, however, constitutive expression of PER, and not CRY1, severely disrupted the clock in fibroblasts and liver. Furthermore, constitutive expression of PER2 in the brain and SCN of transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
268
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(291 citation statements)
references
References 71 publications
(99 reference statements)
15
268
0
1
Order By: Relevance
“…The interaction between PER2 and CK1e is clearly pace-setting, as revealed by accelerated clocks in mutants of CK1e and CK1δ in rodents and humans, respectively, and in the human PER2 FASPS mutant (12) now alongside mouse PER2 Edo . These observations are consistent with the view that the rhythmic availability of PER2 "defines a critical nodal point for negative feedback" within the TTFL (29). Moreover, the Edo mutation accelerates/phase-advances mRNA rhythms in the liver that are, again, as well defined as the mRNA rhythms seen in WT animals.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The interaction between PER2 and CK1e is clearly pace-setting, as revealed by accelerated clocks in mutants of CK1e and CK1δ in rodents and humans, respectively, and in the human PER2 FASPS mutant (12) now alongside mouse PER2 Edo . These observations are consistent with the view that the rhythmic availability of PER2 "defines a critical nodal point for negative feedback" within the TTFL (29). Moreover, the Edo mutation accelerates/phase-advances mRNA rhythms in the liver that are, again, as well defined as the mRNA rhythms seen in WT animals.…”
Section: Discussionsupporting
confidence: 87%
“…It therefore acts as a gain-of-function mutation. We speculate that this gain of function is due to maintenance of normal interactions of PER2 Edo with other clock proteins (e.g., CRY), whereas its more rapid turnover leads to a change in the repressive "nodal set point" established by PER2 (29).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed that FBXL3 interacts with CRY1 and CRY2, promoting the degradation of both these proteins by the ubiquitin/ proteasome system, thus contributing to period length determination (11)(12)(13). However, overexpression of CRY1 protein does not lead to period alteration (14), suggesting that the Fbxl3 mutation might affect additional clock components.…”
mentioning
confidence: 99%
“…The PAS domains mediate homo-and heterodimeric interactions between the mPER homologues (5)(6)(7)(8) as well as interactions of the mPERs with mBMAL1/2, mCLOCK, and NPAS2 (9)(10)(11)(12). These interactions regulate the stability and cellular localization of the mPERs and modulate the activity of the mBMAL1/mCLOCK transcription factor complex.…”
mentioning
confidence: 99%